Hubungan Pendidikan dan Status Kawin dengan Infeksi Menular Seksual pada Wanita Usia Subur di Layanan Klinik IMS - Ayu, Suci Musvita; Susanto, Iwan (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2019)
Background: Sexually Transmitted Infections (STIs) becomes still the main problem of public health in the world. Sexually Transmitted Infections (STIs) are infections that are transmitted through sexual intercourse (vaginal, anal, and oral). The highest of number visited and illnesses of Sexually Transmitted Infections (STIs) in clinics Sexually Transmitted Infections (STIs) Cangkringan Public Health Center will have to appear to affect public health in the district area. This research purpose to determine the relation of level education and marital status with the incidence of STIs on fertile women in clinic IMS. Method: This research was observational analytic research with quantitative methods and cross-sectional design. The population in this study every patient fertile women were examined on clinic Sexually Transmitted Infections (STIs) Cangkringan Public Health Center from January 2016 to July 2016. Samples were 107 respondents taken using a probability sampling technique in which samples using secondary data from inform concent in Public Health Center. Data were analyzed by chi-square test. Result: The result study showed that none significant between level education (RP = 0,796; CI = 0,458-1,382; p-value 0,533) and mental status (RP = 0, 846; CI = 0,168 - 4,264; p-value 1,000) with STIs. Conclusions: It can be concluded that the incidence Sexually Transmitted Infections (STIs) on fertile women in clinic Sexually Transmitted Infections (STIs) Cangkringan Public Health Center not caused by the variable education level and marital status.